Reassessing the Value of Contrast-Enhanced Ultrasonography in Differential Diagnosis of Cervical Tuberculous Lymphadenitis and Lymph Node Metastasis of Papillary Thyroid Carcinoma - Zhang, Xu; Wang, Lingling; Feng, Na; Ni, Tu; Tang, Wei (Frontiers in Oncology, 2021)
Aim We aimed to evaluate the ability of contrast-enhanced ultrasonography (CEUS) to perform differential diagnosis of cervical tuberculous lymphadenitis and lymph node metastasis from papillary thyroid cancer (PTC). Methods We analyzed 102 enlarged cervical lymph nodes as diagnosed by conventional ultrasound (US) and CEUS. The US and CEUS enhancement pattern and the time intensity curve (TIC) of the metastatic lymph nodes or tuberculous lymph nodes were compared following standard pathological protocols. The TIC included peak time (TTP), peak intensity (PI), and area under the gamma curve (AUC). Results Pathological results demonstrated that 48 out of the 102 enlarged lymph nodes were lymph node metastasis from PTC, while 54 were tuberculous lymphadenitis. There was statistically significant differences in hyperechoic islands, pulse-like enhancement, and asynchronous enhancement between tuberculous lymphadenitis and lymph node metastasis (P < 0.05), but their diagnostic sensitivity and specificity were unsatisfactory. In addition, our data did not show statistically significant difference in enhancement direction, enlarged range on CEUS, and perfusion defect (P > 0.05). Similarly, quantitative parameters such as PI, TTP, and AUC did not yield significant differences between the groups. Conclusion Taken together, the present results demonstrate that CEUS can provide valuable information on lymph node blood flow, which can be used to identify tuberculous lymphadenitis and lymph node metastasis of PTC.